2018
DOI: 10.1016/j.stemcr.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Properties of Human Embryonic Stem Cell-Derived Retinal Pigment Epithelial Cells

Abstract: SummaryAge-related macular degeneration is caused by dysfunction and loss of retinal pigment epithelium (RPE) cells, and their transplantation may rescue visual functions and delay disease progression. Human embryonic stem cells (hESCs) may be an unlimited source of RPE cells for allotransplantation. We analyzed the immunomodulatory properties of hESC-derived RPE (hESC-RPE) cells, and showed that they inhibited T cell responses. Co-culture experiments showed that RPE cells inhibited interfon-γ secretion and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…Subgroup analysis was not conducted for awave amplitudes because the subgroups contained too few studies in order to draw meaningful conclusions (less than 4 studies per subgroup remained). For the meta-analysis of ERG b-wave amplitude, twelve [25,29,30,32,33,35,[39][40][41]44,45,49] studies reporting 42 experiments were included, of which 30 experiments were performed in rats and 12 in mice. See Supplementary 1 for all study characteristics of the individual studies.…”
Section: A-wave and B-wave Amplitudes Extracted From Erg Datamentioning
confidence: 99%
“…Subgroup analysis was not conducted for awave amplitudes because the subgroups contained too few studies in order to draw meaningful conclusions (less than 4 studies per subgroup remained). For the meta-analysis of ERG b-wave amplitude, twelve [25,29,30,32,33,35,[39][40][41]44,45,49] studies reporting 42 experiments were included, of which 30 experiments were performed in rats and 12 in mice. See Supplementary 1 for all study characteristics of the individual studies.…”
Section: A-wave and B-wave Amplitudes Extracted From Erg Datamentioning
confidence: 99%
“…IPSCs derived from healthy donors have demonstrated the ability to suppress T-cell activation, induce T-regulatory cells, and secrete immune suppressive factors such as MIF and TGFβ (Sugita et al, 2015). HESCs have also indicated a similar capacity, and appear to have a better immunomodulatory response in the absence of immune suppressive drugs, such as cyclosporine (Idelson et al, 2018).…”
Section: Transplantation and Factors Affecting Integrationmentioning
confidence: 99%
“…We showed that iPSC-RGCs suppressed the immune activity of T-cells via TGF-β. Human corneal endothelial cells, iris pigment epithelial cells and stem cell-derived RPEs have been reported to suppress T-cell activation via TGF-β [4,6,43,44]. In particular, it has been suggested that the induction of regulatory T-cells by TGF-β is involved in the mechanism of inhibition by human corneal endothelial cells and iPSC-RPEs [4,44].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal ganglion cells (RGCs), which are located in the innermost layer of the retina, are responsible for collecting optical information that reaches the retina, and transmitting it to the brain via the optic nerve [ 1 ]. Retinal pigment epithelial cells (RPEs), which are one of the constituent cells of the retina as well as RGCs, have been reported to possess immune-suppression capacity [ 2 , 3 , 4 , 5 , 6 ]. Stem cell-derived RPE transplantation therapy has already been applied clinically [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%